Metajęzykowe oblicze ironii - Starodworskaja, Ekaterina (Studia Rossica Posnaniensia, 2020)
The paper deals with the problem of relations between verbal irony and metalinguistic features of the natural language. It is shown that the irony in the vast majority of situations involves the reaction to a real or imagined speech, which proceeds from the fact that the human mind, the main target of irony, is explicated in a manner making it possible to be examined and evaluated precisely in speech. The target of the irony is man, his intellectual abilities, ethic and aesthetic choices, his views and beliefs, while his speech (word, statement, text, manner of speaking) turns out to be the direct pretext for ironic utterance.